Risk factors for stall unoccupancy in Holstein dairy cows milked 3 times per day in a rotary milking parlor: A case control study - A. Singh; H. Somula; M. Wieland (Journal of Dairy Science)
ABSTRACT: The milking parlor is one of the most expensive capital investments on a dairy, therefore, using it in its most efficient way is crucial to the financial sustainability of dairy operations. Minimizing the number of unoccupied stalls in the parlor is one way to improve the parlor efficiency. Disruption in normal traffic entry to the parlor may lead to an unoccupied stall in front of a cow (i.e., stall unoccupancy). The objectives of this retrospective case control study were to identify cows at risk of stall unoccupancy and to investigate risk factors for stall unoccupancy over a 10-d risk period. The study was conducted on a Holstein dairy farm milking ∼5,000 cows 3 times per day in a 100-stall rotary parlor. Stall unoccupancy in this study refers to an event during milking in which the preceding stall of a cow remained unoccupied. A case of recurrent stall unoccupancy (RSU) was defined as a cow experiencing 11 or more stall unoccupancy events during the 10-d risk period. We hypothesized that certain cows would be responsible for causing RSU and that stall unoccupancy would be associated with cow characteristics, such as parity, stage of lactation, and health-related events. The health events considered were lameness, mastitis, individual quarter dry-off during lactation, vaccination, hoof trimming, and other disease events that occurred 1 wk before, during, or 1 wk following the risk period. Data were extracted from the farm management software programs and analyzed with a multivariable logistic regression model. We found that lactation number, lactation stage, and SCC were associated with RSU. Compared with cows in third or greater lactation, the odds ratio (OR; 95% CI) of RSU were 0.062 (0.03–0.15) for lactation 1 and 0.35 (0.22–0.56) for lactation 2. Taking cows in late lactation (≥200 DIM) as reference group, the OR (95% CI) of RSU were 0.56 (0.35–0.92) for early-lactation (<100 DIM) cows and 0.84 (0.56–1.26) for mid-lactation (101–200 DIM) cows. A 1 unit increase in the log-transformed SCC value was associated with increased odds of RSU (OR [95% CI]: 1.37 [1.05–1.76]). In addition, we documented that lameness was associated with RSU. A cow diagnosed with a lameness event 1 wk before, during, or 1 wk after the risk period exhibited higher odds of RSU with an OR (95% CI) of 1.81 (1.03–3.19). The protocol described herein provides a method to identify cows at risk of RSU and the associated risk factors. Our findings can help dairy producers identify cows that may require assisted entry to the parlor, enabling more efficient use of both parlor and labor resources. In addition to the well-documented effects of lameness on productivity, lactation performance, and animal well-being, our data suggest that lameness can have a substantial effect on parlor efficiency. These findings underscore the importance of effective treatment and prevention strategies for lameness.